Edge Metric Dimension of Some Generalized Petersen Graphs - Filipović, Vladimir; Kartelj, Aleksandar; Kratica, Jozef (Resultate der Mathematik, 2019)
The edge metric dimension problem was recently introduced, which initiated the study of its mathematical properties. The theoretical properties of the edge metric representations and the edge metric dimension of generalized Petersen graphs GP ( n , k ) are studied in this paper. We prove the exact formulae for GP ( n , 1) and GP ( n , 2), while for other values of k a lower bound is stated.